Impact of Antivirals in the Prevention of Serious Outcomes Associated with Influenza in Hospitalized Canadian Adults: A Pooled Analysis from the Serious Outcomes Surveillance (SOS) Network of the Canadian Immunization Research Network (CIRN). (4th October 2017) - Shaffelburg, Zach; Nichols, Michaela; Ye, Lingyun; Andrew, Melissa K; Ambrose, Ardith; Boivin, Guy; Bowie, William R; Chit, Ayman; Santos, Gael Dos; Elsherif, May; Green, Karen; Haguinet, Francois; et al.
Abstract: Background: Antiviral treatment of influenza in outpatient settings is associated with modest improvement in outcomes but benefit in inpatient settings remains unclear. We assessed the impact of antiviral treatment on the severe outcomes death and intensive care unit (ICU) admission and/or need for mechanical ventilation (MV) in hospitalized influenza patients. Methods: Patients admitted to hospitals of the CIRN SOS Network with an acute respiratory illness from 2011/12–2013/14 who tested polymerase chain reaction (PCR) positive for influenza were included. Demographic and medical information were obtained from patient interview or the medical chart. Main outcomes of interest were ICU admission and/or need for MV, and death. Logistic regression with backwards stepwise selection was used to estimate odds ratios (ORs) and 95% confidence limits (CIs) for the association between antiviral use and severe outcomes overall, and stratified by time from symptom onset to antiviral start (<48hours, 48hours <5 days, 5–21 days). Results: Over 3 influenza seasons, 4, 679 patients were enrolled; 59% were aged ≥65 years, 52% were female, and 89% had a comorbidity. Influenza vaccination status was available for 4, 019 (86%) patients, of whom 1, 796 (45%) had received current season vaccine. Of 4, 679 patients, 16% of patients were admitted to ICU and/or required MV and 9% died. Overall, 54% of hospitalized influenza patients received an antiviral; mean time from the onset of symptoms to antiviral start was 4.28 days (range: 0–21 days). Treatment with antivirals was associated with a significant reduction in admission to ICU and/or need for MV (OR = 0.10; 95% CI: 0.08–0.13; P  < 0.001), but was not significantly associated with a reduction in death ( P  = 0.454) irrespective of time between symptom onset and start of antivirals. Conclusion: In this study, treatment with antivirals in hospitalized patients with influenza was associated with a significant reduction in ICU admission and MV, even when initiated a mean of 4.28 days from symptom onset. Reduction in death was not demonstrated. These findings support current recommendations for antiviral use in hospitalized adults and suggest increased compliance with these guidelines may reduce morbidity and cost. Disclosures: M. K. Andrew, GSK: Grant Investigator, Research grant; Pfizer: Grant Investigator, Research grant; Sanofi-Pasteur: Grant Investigator, Research grant; A. Chit, Sanofi pasteur: Employee, Salary; G. Dos Santos, GSK: Employee, Salary; Business and Decision Life Sciences (Contractor for GSK Vaccines): Independent Contractor, Salary; M. Elsherif, Canadian Institutes of Health Research: Investigator, Research grant; Public Health Agency of Canada: Investigator, Research grant; GSK: Investigator, Research grant; F. Haguinet, GSK: Employee, Salary; S. A. Halperin, GSK: Scientific Advisor, Consulting fee; GSK: Grant Investigator, Research grant; T. Hatchette, GSK: Grant Investigator, Grant recipient; Pfizer: Grant Investigator, Grant recipient; Abbvie: Speaker for a talk on biologics and risk of TB reactivation, Speaker honorarium; B. Ibarguchi, GSK: Employee, Salary; J. M. Langley, GSK: Investigator, Research grant; Canadian Institutes of Health Research: Investigator, Research grant; J. Mcelhaney, GSK: Scientific Advisor, Honorarium to institution; Sanofi pasteur: Scientific Advisor, Honorarium to institution; A. Mcgeer, Hoffman La Roche: Investigator, Research grant; GSK: Investigator, Research grant; Sanofi pasteur: Investigator, Research grant; J. Powis, Merck: Grant Investigator, Research grant; GSK: Grant Investigator, Research grant; Roche: Grant Investigator, Research grant; Synthetic Biologicals: Investigator, Research grant; M. Semret, GSK: Investigator, Research grant; Pfizer: Investigator, Research grant; V. Shinde, Novavax: Employee, Salary; GSK: Shareholder, Stocks; GSK: Employee, Salary; S. Trottier, Canadian Institutes of Health Research: Investigator, Research grant; L. Valiquette, GSK: Investigator, Research grant; S. McNeil, GSK: Contract Clinical Trials and Grant Investigator, Research grant; Merck: Contract Clinical Trials and Speaker's Bureau, Speaker honorarium; Novartis: Contract Clinical Trials, No personal renumeration; Sanofi pasteur: Contract Clinical Trials, No personal renumeration